Assessment of the anti microbial spectrum of activity of aloe species found in Zambia( aloe esculenta L.C Leach) on some strains of bacterial and fungi - Kabwe Chitalu Rosemary (Lusaka, the university of Zambia, school of medicine)
Synthetic antimicrobial agentshave been used for the last 70years to treat infectious diseases. Since 1940, these conventional drugs have greatly reduced cases of illness and deaths from infectious diseases.However, these drugs have been used so widely and for a long periods of time such that the infectious organisms that they were designed to kill have adopted them. making the drug less effective and sometimes not effective at all. Therefore this research is to assess the in-vitro anti bacterial and anti fungal spectrum of activitty of aloe esculenta L.C leach.
Dissertation submitted in partial fulfilment for the award of bachelor of pharmacy degree at the university of Zambia.
Keywords: Aloe